PCR-LIS-SSCP (Low ionic strength single-stranded conformation polymorphism)--a simple method for high-resolution allele typing of HLA-DRB1, -DQB1, and -DPB1. - Maruya, E; Saji, H; Yokoyama, S

(untitled) (Genome Research, 1996)
We have developed a simple and efficient procedure with which to form single-stranded DNA [ssDNA] and then applied HLA-DRB1, -DQB1, and -DPB1 allele typing. This method is referred to as low ionic strength single-stranded conformation polymorphism (LIS-SSCP), and is based on the diversity in the electrophoretic mobility of ssDNA formed by heat denaturation in low ionic strength solutions. This method detected DNA polymorphisms, including point mutations at a variety of positions in the DNA fragments of the HLA-DRB1, -DQB1, and -DPB1 genes. Under our experimental conditions, stable ssDNA could be kept at room temperature > or = 5 hr without having been cooled on ice immediately after heat denaturation. A total of 41 HLA-DRB1, 14 HLA-DQB1, and 17 HLA-DPB1 alleles from 220 healthy people were analyzed using a combination of PCR-LIS-SSCP with group-specific amplification. All of the alleles analyzed were discriminated among the DRB1, DQB1, and DPB1 groups except for DPB1*0402 and 0201. The efficiency of ssDNA formation using the LIS-SSCP procedure was higher than that of the traditional formamide method, and the SSCP profiles were clearer than those of the original SSCP. This procedure is useful for screening new alleles as well as the donor-recipient molecular matching of HLA class II genes. It is simple, rapid, and cost effective, requiring neither radioisotopes nor enzymes to confirm the typing results of other methods.